Shoulder dystocia: guidelines for clinical practice from the French College of Gynecologists and Obstetricians (CNGOF). (August 2016) - Sentilhes, Loïc; Sénat, Marie-Victoire; Boulogne, Anne-Isabelle; Deneux-Tharaux, Catherine; Fuchs, Florent; Legendre, Guillaume; Le Ray, Camille; Lopez, Emmanuel; Schmitz, Thomas; Lejeune-Saada, Véronique
Abstract: Shoulder dystocia (SD) is defined as a vaginal delivery in cephalic presentation that requires additional obstetric maneuvers to deliver the fetus after the head has delivered and gentle traction has failed. It complicates 0.5–1% of vaginal deliveries. Risks of brachial plexus birth injury (level of evidence [LE]3), clavicle and humeral fracture (LE3), perinatal asphyxia (LE2), hypoxic-ischemic encephalopathy (LE3) and perinatal mortality (LE2) increase with SD. Its main risk factors are previous SD and macrosomia, but both are poorly predictive; 50–70% of SD cases occur in their absence, and most deliveries when they are present do not result in SD. No study has proven that the correction of these risk factors (except gestational diabetes) would reduce the risk of SD. Physical activity is recommended before and during pregnancy to reduce the occurrence of some risk factors for SD (Grade C). In obese women, physical activity should be coupled with dietary measures to reduce fetal macrosomia and weight gain during pregnancy (Grade A). Women with gestational diabetes require diabetes care (diabetic diet, glucose monitoring, insulin if needed) (Grade A) because it reduces the risk of macrosomia and SD (LE1). Only two measures are proposed for avoiding SD and its complications. First, induction of labor is recommended in cases of impending macrosomia if the cervix is favorable at a gestational age of 39 weeks or more (professional consensus). Second, cesarean delivery is recommended before labor in three situations and during labor in one: (i) estimated fetal weight (EFW) >4500 g if associated with maternal diabetes (Grade C), (ii) EFW >5000 g in women without diabetes (Grade C), (iii) history of SD associated with severe neonatal or maternal complications (professional consensus), and finally during labor, (iv) in case of fetal macrosomia and failure to progress in the second stage, when the fetal head station is above +2 (Grade C). In cases of SD, it is recommended to avoid the following actions: excessive traction on the fetal head (Grade C), fundal pressure (Grade C), and inverse rotation of the fetal head (professional consensus). The McRoberts maneuver, with or without suprapubic pressure, is recommended first (Grade C). If it fails and the posterior shoulder is engaged, Wood's maneuver should be performed preferentially; if the posterior shoulder is not engaged, it is preferable to attempt to deliver the posterior arm next (professional consensus). It appears necessary to know at least two maneuvers to perform should the McRoberts maneuver fail (professional consensus). A pediatrician should be immediately informed of SD. The initial clinical examination should check for complications, such as brachial plexus injury or clavicle fracture (professional consensus). If no complications are observed, neonatal monitoring need not be modified (professional consensus). The implementation of practical training with simulation for all care providers in the delivery room is associated with a significant reduction in neonatal (LE3) but not maternal (LE3) injury. SD remains an unpredictable obstetric emergency. All physicians and midwives should know and perform obstetric maneuvers if needed, quickly but calmly.